Association Between Out-of-Hour Admission and Short- and Long-Term Mortality in Acute Myocardial Infarction: A Systematic Review and Meta-Analysis - Yu, Yue-Yan; Zhao, Bo-Wen; Ma, Lan; Dai, Xiao-Ce (Frontiers in Cardiovascular Medicine, 2021)
Objectives: Out-of-hour admission (on weekends, holidays, and weekday nights) has been associated with higher mortality in patients with acute myocardial infarction (AMI). We conducted a meta-analysis to verify the association between out-of-hour admission and mortality (both short- and long-term) in AMI patients. Design: This Systematic review and meta-analysis of cohort studies. Data sources: PubMed and EMBASE were searched from inception to 27 May 2021. Eligibility criteria for selected studies: Studies of any design examined the potential association between out-of-hour admission and mortality in AMI. Data extraction and synthesis: Two investigators extracted the data and evaluated the risk of bias. Analysis was conducted using a random-effects model. The results are shown as odds ratios [ORs] with 95% confidence intervals (CIs). I2 value was used to estimate heterogeneity. Grading of Recommendations Assessment, Development, and Evaluation was used to assess the certainty of the evidence. Results: The final analysis included 45 articles and 15,346,544 patients. Short-term mortality (defined as either in-hospital or 30-day mortality) was reported in 42 articles (15,340,220 patients). Out-of-hour admission was associated with higher short-term mortality (OR 1.04; 95%CI 1.02-1.05; I2=69.2%) but there was a significant statistical indication for publication bias (modified Macaskill’s test P<.001). One-year mortality was reported in 10 articles (1,386,837 patients). Out-of-hour admission was also associated with significantly increased long-term mortality (OR 1.03; 95%CI 1.01-1.04; I2=66.6%), with no statistical indication of publication bias (p = 0.207). In the exploratory subgroup analysis, the intervention effect for short-term mortality was pronounced among patients in different regions (p=.04 for interaction) and socio-economic levels (p=.007 for interaction) and long-term mortality was pronounced among patients with different type of AMI (p=.0008 for interaction) or on different types of out-to-hour admission (p=.006 for interaction). Conclusion: Out-of-hour admission may be associated with an increased risk of both short- and long-term mortality in AMI patients. Trial registration: PROSPERO (CRD42020182364).